2006
DOI: 10.1245/s10434-006-9076-y
|View full text |Cite
|
Sign up to set email alerts
|

Hematoma-Directed Ultrasound-Guided (HUG) Breast Lumpectomy

Abstract: This study suggests that HUG is more accurate in localizing non-palpable lesions than NLBB. By eliminating the additional procedure needed for NLBB, HUG may also be more time- and cost efficient. HUG makes VABB not only a less invasive diagnostic procedure, but also a localization procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…After every biopsy, a hematoma remains within the biopsy site. Thompson and colleagues hypothesized that the hematoma could be used as a physiological marker that can be detected via ultrasound at the time of resection, 3 and introduced the term hematoma ultrasound-guided to describe the procedure. They have subsequently reported their 10-year successful experience with this method, 14 showing HUG lumpectomy to be safe and accurate in their practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After every biopsy, a hematoma remains within the biopsy site. Thompson and colleagues hypothesized that the hematoma could be used as a physiological marker that can be detected via ultrasound at the time of resection, 3 and introduced the term hematoma ultrasound-guided to describe the procedure. They have subsequently reported their 10-year successful experience with this method, 14 showing HUG lumpectomy to be safe and accurate in their practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several alternatives to NL, for example, radioactive seed implantation and MRI guidance, have been suggested. 1,2 Thompson and colleagues demonstrated that intraoperative localization of the biopsy hematoma (hematoma ultrasound-guided [HUG] lumpectomy) could eliminate the need for NL 3 without introducing the need for another invasive procedure. Hematoma ultrasound guidance was incorporated into our practice at the University of Iowa Hospitals and Clinics in 2007.…”
mentioning
confidence: 99%
“…3 The obvious benefit for the patient is that he or she does not need to undergo a secondary localization procedure. 4 We and others have demonstrated the usefulness of intraoperative US after a positive stereotactic core biopsy that results in the need for BCS therapy. The patients traditionally require needle localization breast biopsy (NLBB), a most barbaric procedure during which 10-20 % of patients faint or vomit due to vasovagal reflex.…”
Section: Further Use Of Image-guided Us In Both the Operating Room Anmentioning
confidence: 97%
“…We termed this the hematoma-directed ultrasound-guided (HUG) procedure. 4 Arentz et al7 demonstrated better margin clearance than with traditional NLBB. In addition, a recent study…”
mentioning
confidence: 98%
“…In addition, hematoma formation may disperse cells to even larger volumes. For these reasons VAB procedures have been shown to limit breast conservative surgery in up to 30 % of the cases [3,4,5]. If multiple stereotactic macrobiopsies decrease the likelihood of breast conservation surgery, this important advantage of early detection might be lost.…”
Section: Introductionmentioning
confidence: 99%